A Cell-based Model of Hemostasis - Hoffman, Maureane; Monroe, Dougald M., III (Thrombosis and Haemostasis, 2001)
Based on our work and that of many other workers, we have developed a model of coagulation in vivo. Many workers have demonstrated mechanisms by which cells can influence the coagulation process. Nonetheless, the prevailing view of hemostasis remains that the protein coagulation factors direct and control the process with cells serving primarily to provide a phosphatidylserine containing surface on which the procoagulant complexes are assembled. By contrast, we propose a model in which coagulation is regulated by properties of cell surfaces. This model emphasizes the importance of specific cellular receptors for the coagulation proteins. Thus, cells with similar phosphatidylserine content can play very different roles in hemostasis depending on their complement of surface receptors. We propose that coagulation occurs not as a “cascade”, but in three overlapping stages: 1) initiation, which occurs on a tissue factor bearing cell; 2) amplification, in which platelets and cofactors are activated to set the stage for large scale thrombin generation; and 3) propagation, in which large amounts of thrombin are generated on the platelet surface. This cell based model explains some aspects of hemostasis that a protein-centric model does not.
Keywords: Blood coagulation; tissue factor; platelets